Tracking control for switched nonlinear systems with multiple time-varying delays. (August 2015) - Zhai, Jun-yong; Wang, Bin; Fei, Shu-min
Abstract: This paper investigates the problem of output tracking control for a class of switched nonlinear systems with multiple time-varying delays. Combining average dwell-time with free weighting matrix methods, a new exponential stability criterion is derived for switched nonlinear systems, which considers the time-varying delays and the rates of time delays. Then, the state feedback tracking controller is given by solving a set of linear matrix inequalities (LMIs) to satisfy the H ∞ model reference tracking performance. Finally, a simulation example is given to illustrate the effectiveness of the proposed method.